Construction method of aluminum surface microchannel, anodic oxidation electrolyte of aluminum surface microchannel and application of aluminum surface microchannel
A strong alkaline anodizing electrolyte with film-forming agents and promoters forms uniform microchannels on aluminum surfaces, addressing corrosion and uniformity issues, enhancing boiling heat transfer efficiency.
Patent Information
- Application Number
- CN202311653362.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-04
- Publication Date
- 2024-12-31
AI Technical Summary
Existing methods for constructing microchannels on complex metal structures, such as anodizing aluminum, face issues with corrosion and poor pore uniformity under acidic conditions, while alkaline systems suffer from low porosity and poor pore uniformity.
A strong alkaline anodizing electrolyte containing a film-forming agent, promoter, and auxiliary agent is used to form uniform, dense microchannels on aluminum surfaces, utilizing magnetron sputtering for coating and electrolytic polishing to enhance the anodization process.
The method achieves orderly, continuous, and complete microchannel structures on aluminum surfaces, significantly improving boiling heat transfer efficiency by up to 5 times compared to traditional methods.
Smart Images

Figure CN119221066A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal surface treatment, and in particular to a method for constructing an aluminum surface microchannel, an anodic oxidation electrolyte and an application thereof. Background Art
[0002] Microchannel heat transfer technology has been widely used in electronic heat dissipation, optoelectronics, chemical industry and other fields due to its high heat transfer efficiency, large specific surface area and small scale. However, existing laser etching, micro-drilling, micro-milling and other methods cannot meet the requirements of processing microchannels on the surface of complex metal structures. Anodizing of aluminum is an economical, simple and effective surface microchannel preparation technology. It is widely used in the construction of microchannel structures on the surfaces of large-area and complex curved structures and in improving the oxidation, corrosion and wear properties of aluminum surfaces. Traditional anodizing of aluminum is mostly carried out under acidic conditions. The anodizing process under acidic conditions will cause serious corrosion of the non-aluminum-plated part of the surface of the metal structure, thereby affecting the integrity of the metal structure. Most metal materials are relatively stable in an alkaline environment, so it is very necessary to develop a porous alkaline anodizing process.
[0003] At present, there are few reports on the preparation of anodized film with uniform pore structure by anodizing aluminum materials under alkaline conditions. The Chinese invention patent (application number: 201810659854.9) "An alkaline anodizing solution for aluminum products and anodizing method" uses a weak alkaline salt alcohol solution system to prepare an anodized film on the surface of aluminum products. However, the inventor of the present invention found that the anodizing process of aluminum products in traditional acidic electrolytes leads to the generation and growth of porous oxide films due to the strong "acidic field-induced dissolution" effect, while the weak alkaline salt alcohol electrolyte system has a low porosity and poor pore uniformity due to the weak "alkaline field-induced dissolution" force and the inhibitory effect of alcohol. Based on the above application background and existing problems, this invention is specially proposed. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention aims to provide a method for constructing aluminum surface microchannels, an anodic oxidation electrolyte and applications thereof.
[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0006] In a first aspect, the present invention provides an anodizing electrolyte for constructing aluminum surface microchannels, wherein the solutes in the anodizing electrolyte include a film-forming agent, a film-forming promoter and a film-forming auxiliary agent; the film-forming agent includes a strong base, the film-forming promoter includes an alkali metal pyrophosphate and / or an alkali metal polyphosphate, and the film-forming auxiliary agent includes an alkali metal weak acid salt.
[0007] In a second aspect, the present invention further provides a method for constructing an aluminum surface microchannel, comprising:
[0008] contacting the aluminum surface with the anodizing electrolyte;
[0009] The aluminum surface is used as an anode, and current is applied to the aluminum surface for anodization to form a microchannel.
[0010] In a third aspect, the present invention further provides a boiling heat transfer component, the surface of which has aluminum surface microchannels constructed by the above construction method.
[0011] In a fourth aspect, the present invention further provides the application of the above-mentioned boiling heat transfer component in any field of electronic heat dissipation, optoelectronics, and chemical industry.
[0012] Correspondingly, the above application includes a boiling heat transfer method, which includes contacting the boiling heat transfer component with a heat-conducting liquid to transfer heat by boiling.
[0013] Based on the above technical solution, compared with the prior art, the beneficial effects of the present invention at least include:
[0014] The anodizing electrolyte and the method for constructing aluminum surface microchannels provided by the present invention can form an orderly, continuous, dense and complete microchannel pore structure on the aluminum surface through the electrolytic oxidation of a strong alkaline electrolyte, forming a microstructure that is extremely suitable for boiling heat transfer of liquid on the surface, thereby significantly improving the boiling heat transfer efficiency of the aluminum surface.
[0015] The above description is only an overview of the technical solution of the present invention. In order to enable those skilled in the art to more clearly understand the technical means of the present application and implement them according to the contents of the specification, the following is a description of the preferred embodiments of the present invention in conjunction with detailed drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a comparison photo of the oxidation objects in different anodizing methods provided in a typical implementation case of the present invention;
[0017] Figure 2a This is an electron microscope photograph of an aluminum surface formed by weakly alkaline anodization provided in a typical comparative example of the present invention;
[0018] Figure 2b This is an electron microscope photograph of an aluminum surface formed by strong alkaline anodization provided in a typical implementation case of the present invention. DETAILED DESCRIPTION
[0019] In view of the deficiencies in the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution, its implementation process and principle will be further explained as follows. The purpose of the present invention is to provide an alkaline anodizing preparation method suitable for preparing a porous structure on the surface of aluminum products, especially to provide a method for constructing microchannels on the surface of metal materials with a wide range of applications and good reliability.
[0020] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0021] An embodiment of the present invention provides an anodizing electrolyte for constructing aluminum surface microchannels, wherein the solute in the anodizing electrolyte includes a film-forming agent, a film-forming promoter, and a film-forming auxiliary agent; the film-forming agent includes a strong base, the film-forming promoter includes an alkali metal pyrophosphate and / or an alkali metal polyphosphate, and the film-forming auxiliary agent includes an alkali metal weak acid salt.
[0022] In some embodiments, the film-forming agent includes any one of sodium hydroxide, potassium hydroxide, lithium hydroxide, barium hydroxide, and cesium hydroxide, or a combination of two or more thereof.
[0023] In some embodiments, the film-forming promoter includes any one of sodium pyrophosphate, potassium pyrophosphate, sodium polyphosphate, potassium polyphosphate, or a combination of two or more thereof.
[0024] In some embodiments, any one of sodium citrate, sodium acetate, sodium oxalate, potassium sodium tartrate, sodium tetraborate, or a combination of two or more thereof.
[0025] As for the specific composition ratio, in some embodiments, the concentration of the film-forming agent in the anodizing electrolyte is 30 to 90 g / L.
[0026] In some embodiments, the concentration of the film-forming promoter in the anodizing electrolyte is 20 to 40 g / L.
[0027] In some embodiments, the concentration of the film-forming aid in the anodizing electrolyte is 25 to 60 g / L.
[0028] Based on the above ratio, in some embodiments, the pH value of the anodizing electrolyte is 12-14.
[0029] As some typical application examples, in the provided anodizing electrolyte, the film-forming agent refers to a mixture of one or more of 0-30g sodium hydroxide, 0-40g potassium hydroxide, 0-35g lithium hydroxide, 0-25g barium hydroxide, and 0-20g cesium hydroxide, calculated on a per liter basis of deionized water; the film-forming promoter refers to a mixture of one or more of 0-10g sodium pyrophosphate, 0-15g potassium pyrophosphate, 0-15g sodium polyphosphate, and 0-10g potassium polyphosphate, calculated on a per liter basis of deionized water; the auxiliary film-forming agent refers to a compound of 0-10g sodium citrate, 0-10g sodium acetate, 0-15g sodium oxalate, 0-20g potassium sodium tartrate, and 0-25g sodium tetraborate, calculated on a per liter basis of deionized water.
[0030] As an application of the above-mentioned anodizing electrolyte, an embodiment of the present invention further provides a method for constructing aluminum surface microchannels, which comprises the following steps:
[0031] The aluminum surface is contacted with the anodizing electrolyte provided by any of the above embodiments.
[0032] The aluminum surface is used as an anode, and current is applied to the aluminum surface for anodization to form a microchannel.
[0033] As some typical application examples of the above technical solution, taking the construction of abundant microchannels on the surface of metal material for surface boiling heat transfer as an example, a method for constructing microchannels on the surface of metal material is illustrated, comprising the following steps:
[0034] S1. Use magnetron sputtering technology to deposit a titanium metal transition layer and an aluminum metal coating on the surface of the metal material.
[0035] S2. Constructing highly ordered microchannels on the surface of the aluminum metal coating deposited in step S1 by strong alkaline anodizing technology.
[0036] Regarding the formation process of the aluminum surface, in some embodiments, the aluminum surface can be, for example, the surface of a layer of aluminum metal coating plated on the surface of the base component. Of course, feasible implementations are not limited to this, and the surface of the entire aluminum structure can still constitute the above-mentioned "aluminum surface", and the above-mentioned anodizing electrolyte and the corresponding microchannel construction method are applied.
[0037] Corresponding to the above-mentioned implementation of the aluminum metal coating, in some embodiments, the construction method may specifically include the following steps:
[0038] The basic component is provided, and a transition layer is plated on the surface of the basic component.
[0039] The aluminum metal coating is plated on the surface of the transition layer to form the aluminum surface.
[0040] In some more preferred embodiments, the transition layer and the aluminum metal coating are plated by magnetron sputtering. Magnetron sputtering is a technology that can prepare metal / non-metal coatings on the surfaces of various substrates by atomization of deposited elements under vacuum conditions. The particles sputtered by magnetron sputtering technology have high energy, dense coatings, and good coating / substrate bonding. The consistency of the coating can still be ensured on the metal surface, and it is suitable for large-area uniform plating. However, the feasible implementation scope is not limited to this. The same film structure can be prepared by forming the transition layer + aluminum metal coating in the form of other methods such as evaporation, electrochemical plating, etc.
[0041] As a typical application example, the magnetron sputtering process of the metal transition layer and the aluminum metal coating is as follows: for example, step S1 in the above exemplary scheme specifically includes: in a vacuum degree of 1×10 -6 In the argon environment of the support, first set the power to 360W and the duty cycle to 50% to plasma clean the surface of the metal structure, and then maintain the vacuum degree of the argon atmosphere at 0.4Pa, the power to 300W, the duty cycle to 50%, formally sputter the titanium metal transition layer for 30 minutes, and then sputter the aluminum metal coating, the sputtering time is 8 hours.
[0042] As for the specific material selection, in some embodiments, the material of the transition layer includes any one of titanium and chromium or a combination of two or more thereof.
[0043] In some embodiments, the material of the base component includes any one or a combination of two or more of metal, carbon material and polymer material; for example, the metal material refers to stainless steel, copper alloy, high temperature alloy, Hastelloy and other materials, but not limited to these; the carbon material and ceramic material layer can be selected as non-metallic materials with better thermal conductivity, such as diamond, etc., but also not limited to these.
[0044] Regarding the thickness of the film layer, in some embodiments, the thickness of the transition layer is 0.1 to 0.5 μm.
[0045] In some embodiments, the aluminum metal coating has a thickness of 5 to 20 μm.
[0046] In order to further improve the quality of anodization and construct more orderly and uniform microchannels, in some embodiments, before the anodization, the method further includes: performing an electrolytic polishing treatment on the aluminum surface.
[0047] The specific electrolytic polishing process can be adaptively selected or replaced by other forms of polishing methods; and as an example, the strong alkaline anodizing technology treatment method in step S2 is as follows:
[0048] S2-1. Place the treated aluminum metal coating specimen in a mixed solution of anhydrous ethanol and perchloric acid in a volume ratio of 4:1 for electropolishing, using a high-purity graphite plate as the cathode. The electropolishing conditions are a processing voltage of 20V, a processing temperature of 0℃, and a processing time of 30s. After polishing, clean it with anhydrous ethanol and deionized water in turn and set it aside.
[0049] S2-2. Place the electropolished specimen in an alkaline anodizing electrolyte, use a stainless steel plate as the cathode, start circulating cooling, and use a DC regulated power supply to perform anodizing treatment on the treated specimen. After completion, take out the specimen and rinse it with deionized water and blow dry it with cold air.
[0050] As for the process conditions during anodization, the voltage of anodization is 10-80V; in some implementation schemes, the plate spacing is, for example, about 5cm, and the plate spacing setting can be referred to the existing anodization scheme. For example, in a limited number of experiments, it can be set to 3-8cm, but it is not limited to this.
[0051] In some embodiments, the temperature of the anodization is about 40° C., such as 35-45° C., and the time is 15-60 minutes. Of course, this is not limited to this, and those skilled in the art can determine the optimal parameters according to orthogonal experiments.
[0052] In some embodiments, the anodization is performed in a constant voltage mode.
[0053] Based on the above preparation method, in some embodiments, the porosity of the microchannels on the aluminum surface is between 10% and 50%.
[0054] In some embodiments, the depth of the microchannels on the aluminum surface is between 0.1 μm and 8 μm.
[0055] The present invention first provides an anodic oxidation electrolyte suitable for making a surface microstructure for boiling heat transfer, and provides a corresponding anodic oxidation method, which is also a method for constructing a surface microstructure; based on the above technical scheme, an embodiment of the present invention also provides a boiling heat transfer component, the surface of the boiling heat transfer component has aluminum surface microchannels constructed by the above construction method.
[0056] Furthermore, the embodiments of the present invention also provide the application of the boiling heat transfer component in any field of electronic heat dissipation, optoelectronics, and chemical industry.
[0057] This application is, for example, a boiling heat transfer method, that is, using the above-mentioned boiling heat transfer component as a heating element or a heat conductor, making it contact with a liquid heat-conducting material, and heating the liquid heat-conducting material to perform boiling heat transfer on its microstructured surface; the present invention does not impose too many restrictions on the specific boiling heat transfer method, and those skilled in the art may make settings with reference to the existing technology, or design and develop it on their own.
[0058] Based on the above technical scheme, the present invention adds a phosphate film-forming promoter to the strongly alkaline anodizing electrolyte, which can form a passivation film on the surface of the aluminum product during the anodizing process, reduce the dissolution rate of the anodized film while maintaining the uniformity of the pore structure of the anodized film, thereby ensuring the continuity of the growth of the anodized film and the integrity of the pore structure; the auxiliary film-forming agent used can improve the stability of the alkaline anodizing electrolyte, so that the growth process of the anodized film can proceed stably.
[0059] The present invention utilizes magnetron sputtering technology to realize the preparation of surface aluminum metal coatings that are not restricted by substrate materials and shape and size. At the same time, the synergistic effect of strongly alkaline film-forming agents, film-forming promoters and auxiliary film-forming agents is utilized to enable the aluminum metal coating to stably undergo an anodic oxidation reaction in an alkaline electrolyte and maintain the integrity of the pore structure during the anodization process, thereby realizing the construction of different metal surface microchannel structures.
[0060] Compared with the surface microchannels formed by the prior art solutions, the finally formed aluminum surface microchannels have uniform size distribution, continuity, strong integrity, and high density, which is very beneficial to improving the efficiency of boiling heat transfer and achieves significant progress.
[0061] For further understanding, the technical solution of the present invention is further described in detail below through several embodiments and in conjunction with the accompanying drawings. However, the selected embodiments are only used to illustrate the present invention, and do not limit the scope of the present invention.
[0062] It should be noted that the base materials used in the following embodiments are as follows:
[0063] 1. The stainless steel material model is 316L, and its composition is: C≤0.03%, Si≤1%, Mn≤2%, S≤0.03%, P≤0.045%, 16%~18% Cr, 10%~14% Ni, 2%~3% Cr, and the balance is Fe.
[0064] 2. The copper alloy material model is H62, and its composition is: 60.5%~63.5% Cu, Fe≤0.15%, Pb≤0.08%, Sb≤0.005%, Bi≤0.002%, P≤0.001%, and the balance is Zn.
[0065] 3. The high-temperature alloy material model is GH4169, and its composition is: 50%~55% Ni, 17%~21% Cr, Fe≤11%, Mo≤3%, 0.2%~0.8% Al, 0.6%~1.2% Ti, C≤0.08%, Mn≤0.35%, Si≤0.35, S≤0.015%, P≤0.02%, B≤0.01%.
[0066] 4. The material model of Hastelloy alloy is C276, and its composition is: Ni≥57%, 15%~17% Mo, 14.5%~16.5% Cr, 4%~7% Fe, Co≤2.5%, C≤0.01%, Mn≤1%, Si≤0.08%, P≤0.04%, 3%~4.5% W.
[0067] In addition, unless otherwise specified, the reagents, raw materials, equipment, and testing instruments used in the embodiments of the present invention are all conventionally purchased or conventionally used.
[0068] Example 1
[0069] A method for constructing a microchannel on the surface of a metal material comprises the following steps:
[0070] (1) First, magnetron sputtering technology was used to obtain a vacuum of 1×10 -6 In the argon environment of the support, the surface of the structural material is plasma cleaned under the conditions of power of 360w and duty cycle of 50%, and then the argon atmosphere vacuum is maintained at 0.4Pa, the power is 300w, the duty cycle is 50%, and the titanium metal transition layer is formally sputtered for 30min, and then the aluminum metal coating is sputtered for 8h to obtain the aluminum metal coating part on the surface of the metal material. Among them, the thickness of the titanium layer is 0.3μm, and the thickness of the aluminum layer is 10μm.
[0071] (2) Surface polishing:
[0072] The aluminum metal coating specimen after magnetron sputtering was placed in a mixed solution of anhydrous ethanol and perchloric acid with a volume ratio of 4:1 for electropolishing, with a high-purity graphite plate as the cathode. The electropolishing conditions were a processing voltage of 20V, a processing temperature of 0°C, and a processing time of 30s. After polishing, it was cleaned with anhydrous ethanol and deionized water in turn and set aside.
[0073] (3) preparing an acidic anodic oxidation electrolyte, a weakly alkaline anodic oxidation electrolyte and the alkaline anodic oxidation electrolyte of the present invention:
[0074] Control group 1) The acidic anodizing electrolyte adopts the conventional sulfuric acid anodizing electrolyte formula, configures 220g / L sulfuric acid electrolyte, adopts the anodizing voltage of 15V, the temperature of 25℃, the treatment time of 15min, and carries out acidic anodizing treatment on the surface of the aluminum metal coating specimen of the stainless steel.
[0075] Control group 2) The weakly alkaline anodizing electrolyte was prepared according to Example 1 shown in the Chinese patent (application number: 201810659854.9) "An alkaline anodizing liquid for aluminum products and anodizing method", wherein the sodium carbonate content was 40 g / L, the boric acid content was 5 g / L, the glycerol content was 70 g / L, the anodizing voltage was 80 V, the temperature was 80 ° C, the treatment time was 90 min, and alkaline anodizing treatment was carried out on the surface of the aluminum metal coating specimen of the stainless steel.
[0076] Experimental group 3) The strong alkaline anodizing electrolyte was prepared by adding 55 g / L of a film-forming agent, 25 g / L of a film-forming promoter, and 35 g / L of an auxiliary film-forming agent to deionized water, and mixing them evenly to obtain an alkaline anodizing electrolyte.
[0077] Wherein: the film-forming agent refers to 30g of sodium hydroxide, 10g of potassium hydroxide, 5g of lithium hydroxide, 5g of barium hydroxide, and 5g of cesium hydroxide based on 1L of deionized water.
[0078] The film-forming accelerator is composed of 10g sodium pyrophosphate, 5g potassium pyrophosphate and 10g potassium polyphosphate based on 1L of deionized water.
[0079] The auxiliary film-forming agent refers to 5g of sodium citrate, 10g of sodium acetate, 5g of sodium oxalate, 10g of potassium sodium tartrate, and 5g of sodium tetraborate based on 1L of deionized water.
[0080] (4) Using a metal surface aluminum coating specimen selected from stainless steel, copper alloy, high temperature alloy, and Hastelloy as the anode and stainless steel as the cathode, immerse the treated specimen in an alkaline anodizing electrolyte, start circulating cooling, and use a DC regulated power supply in constant voltage mode at a voltage of 40 V to perform anodizing treatment on the treated specimen for 30 minutes. After completion, take out the specimen and rinse it with deionized water and dry it.
[0081] It should be noted that, although the voltage, temperature and electrolysis time used in the control group and the experimental group are different, different electrolyte systems match different optimal process conditions. The above process conditions are all based on the optimal parameter combination that can be obtained for the corresponding electrolyte system established by orthogonal experiments (established based on the goal of maximizing boiling heat transfer efficiency), that is, the results corresponding to the process conditions in the above embodiments are already the optimal values that can be achieved by the corresponding electrolyte system.
[0082] Figure 1 The (a) panel is a macroscopic optical photograph of the aluminum metal coating on the surface of stainless steel after acid anodizing. The (c) panel is a macroscopic optical photograph of the aluminum metal coating on the surface of stainless steel after alkaline anodizing. Figure 2a This is a microstructure photo of the aluminum metal coating on the surface of stainless steel after being treated in a weakly alkaline anodizing electrolyte. Figure 2b This is a microstructure photograph of a stainless steel surface aluminum metal coating specimen after being treated in the alkaline anodizing electrolyte described in the present invention.
[0083] from Figure 1 It can be seen from the figure that compared with traditional acidic anodizing, anodizing under alkaline conditions has no corrosion to the stainless steel substrate material; it can be seen from Figure 2 that the surface microchannel structure of the oxide film obtained in the alkaline anodizing electrolyte of the present invention is more uniform, the porosity is higher, and the distribution of pores is more uniform, the pore structure is more complete, and even some parts are similar to a honeycomb state.
[0084] Compared with the stainless steel substrate, the boiling heat transfer efficiency of the components treated with the strong alkaline anodizing electrolyte increased by about 4 times. In contrast, the boiling heat transfer efficiency of the components treated with the weak alkaline anodizing electrolyte increased by only 57%, and the boiling heat transfer efficiency of the components treated with the acidic anodizing electrolyte increased by only 87%, which were significantly weaker than the strong alkaline anodizing electrolyte.
[0085] It can be seen from this that the surface microchannel structure construction method under the process conditions provided in this embodiment is also applicable to aluminum metal coating test pieces on the surfaces of copper alloys, high-temperature alloys, and Hastelloy alloys.
[0086] Comparative Example 1
[0087] This comparative example is substantially the same as Example 1, except that:
[0088] When magnetron sputtering aluminum, the thickness of the aluminum layer was adjusted to prepare two samples:
[0089] a. The thickness of the aluminum layer is relatively thick, which is 5μm; b. The thickness of the aluminum layer is relatively thin, which is 25μm.
[0090] It was finally found that the improvement in boiling heat transfer efficiency provided by the above-mentioned control samples a and b were significantly lower than that in Example 1, with the specific values being 1 times for sample a and 1 times for sample b. Surface electron microscopy revealed that although the pore depth of sample a was sufficient, multiple pores merged and collapsed, seriously affecting the integrity of the pores. Sample b did not form an efficient and ordered microchannel structure due to insufficient pore depth.
[0091] Similarly, using a whole piece of aluminum material to construct the surface microstructure will also face the same technical problems as the aluminum layer, which is not conducive to achieving the best boiling heat transfer efficiency. However, this does not mean that this implementation is not within the feasible scope of the present invention, it is only a suboptimal solution.
[0092] Example 2
[0093] A method for constructing a microchannel on the surface of a metal material comprises the following steps:
[0094] (1) Steps 1 and 2 of the specimen treatment before alkaline anodization are the same as those in Example 1.
[0095] (2) Preparation of alkaline anodizing electrolyte:
[0096] A film-forming agent with a concentration of 90 g / L, a film-forming accelerator with a concentration of 20 g / L, and an auxiliary film-forming agent with a concentration of 25 g / L were added to deionized water, and the mixture was evenly mixed to obtain an alkaline anodizing electrolyte.
[0097] Wherein: the film-forming agent refers to 10g of sodium hydroxide, 40g of potassium hydroxide, 5g of lithium hydroxide, 25g of barium hydroxide, and 10g of cesium hydroxide based on 1L of deionized water.
[0098] The film-forming accelerator is composed of 15g potassium pyrophosphate and 5g sodium polyphosphate based on 1L of deionized water.
[0099] The auxiliary film-forming agent is composed of 10g sodium citrate, 5g potassium sodium tartrate and 5g sodium tetraborate based on 1L of deionized water.
[0100] (3) Use a metal surface aluminum coating specimen selected from stainless steel, copper alloy, high-temperature alloy, and Hastelloy as the anode and stainless steel as the cathode. Immerse the treated specimen in an alkaline anodizing electrolyte, start circulating cooling, and use a DC regulated power supply in constant voltage mode. Anodize the treated specimen at a voltage of 10 V for 15 minutes. After completion, take out the specimen and rinse it with deionized water and dry it.
[0101] The microchannel pore structure on the surface of stainless steel, copper alloy, high-temperature alloy, and Hastelloy aluminum-coated specimens prepared under this process condition is also good, and can also achieve a similar degree of improvement in boiling heat transfer efficiency.
[0102] Example 3
[0103] A method for constructing a microchannel on the surface of a metal material comprises the following steps:
[0104] (1) Steps 1 and 2 of the specimen treatment before alkaline anodization are the same as those in Example 1.
[0105] (2) Preparation of alkaline anodizing electrolyte:
[0106] A film-forming agent with a concentration of 30 g / L, a film-forming accelerator with a concentration of 40 g / L, and an auxiliary film-forming agent with a concentration of 60 g / L were added to deionized water, and the mixture was evenly mixed to obtain an alkaline anodizing electrolyte.
[0107] Wherein: the film-forming agent refers to 5g of lithium hydroxide, 5g of barium hydroxide, and 20g of cesium hydroxide based on 1L of deionized water.
[0108] The film-forming accelerator is composed of 10g sodium pyrophosphate, 15g potassium pyrophosphate and 15g sodium polyphosphate based on 1L of deionized water.
[0109] The auxiliary film-forming agent refers to 5g of sodium citrate, 15g of sodium oxalate, 15g of potassium sodium tartrate, and 25g of sodium tetraborate based on 1L of deionized water.
[0110] (3) A specimen with aluminum coating on the surface of one of the metals selected from stainless steel, copper alloy, high-temperature alloy, and Hastelloy is used as the anode and stainless steel as the cathode. The treated specimen is immersed in an alkaline anodizing electrolyte. The circulating cooling is turned on. A DC regulated power supply is used in constant voltage mode. The treated specimen is anodized for 60 minutes at a voltage of 80 V. After completion, the specimen is taken out and rinsed with deionized water and dried.
[0111] The surface microchannel structures of stainless steel, copper alloy, high-temperature alloy, and Hastelloy aluminum metal coating specimens prepared under this process condition are also good, and can also achieve similar improvements in boiling heat transfer efficiency.
[0112] Example 4
[0113] A method for constructing a microchannel on the surface of a metal material comprises the following steps:
[0114] (1) Steps 1 and 2 of the specimen treatment before alkaline anodization are the same as those in Example 1.
[0115] (2) Preparation of alkaline anodizing electrolyte:
[0116] Add 70 g / L of a film-forming agent, 22 g / L of a film-forming accelerator, and 30 g / L of an auxiliary film-forming agent into deionized water, mix them evenly, and obtain an alkaline anodizing electrolyte.
[0117] Wherein: the film-forming agent refers to 10g of sodium hydroxide, 10g of potassium hydroxide, 35g of lithium hydroxide, and 15g of barium hydroxide based on 1L of deionized water.
[0118] The film-forming accelerator is composed of 5g of sodium pyrophosphate, 12g of potassium pyrophosphate, and 5g of potassium polyphosphate based on 1L of deionized water.
[0119] The auxiliary film-forming agent refers to 5g of sodium acetate, 20g of potassium sodium tartrate, and 5g of sodium tetraborate based on 1L of deionized water.
[0120] (3) A specimen with aluminum coating on the surface of one of the metals selected from stainless steel, copper alloy, high-temperature alloy and Hastelloy is used as the anode and stainless steel as the cathode. The treated specimen is immersed in an alkaline anodizing electrolyte. The circulating cooling is turned on. A DC regulated power supply is used in constant voltage mode. The treated specimen is anodized for 25 minutes at a voltage of 25 V. After completion, the specimen is taken out and rinsed with deionized water and dried.
[0121] The surface microchannel structures of stainless steel, copper alloy, high-temperature alloy, and Hastelloy aluminum metal coating specimens prepared under this process condition are also good, and can also achieve similar improvements in boiling heat transfer efficiency.
[0122] Example 5
[0123] A method for constructing a microchannel on the surface of a metal material comprises the following steps:
[0124] (1) Steps 1 and 2 of the specimen treatment before alkaline anodization are the same as those in Example 1.
[0125] (2) Preparation of alkaline anodizing electrolyte:
[0126] A film-forming agent with a concentration of 45 g / L, a film-forming accelerator with a concentration of 30 g / L, and an auxiliary film-forming agent with a concentration of 45 g / L were added to deionized water, and the mixture was evenly mixed to obtain an alkaline anodizing electrolyte.
[0127] Wherein: the film-forming agent refers to 10g of lithium hydroxide, 25g of barium hydroxide, and 10g of cesium hydroxide based on 1L of deionized water.
[0128] The film-forming accelerator is composed of 15g of sodium pyrophosphate and 15g of potassium pyrophosphate based on 1L of deionized water.
[0129] The auxiliary film-forming agent refers to 10g of sodium citrate, 10g of sodium oxalate, 10g of potassium sodium tartrate, and 15g of sodium tetraborate based on 1L of deionized water.
[0130] (3) Using a metal surface aluminum coating specimen selected from stainless steel, copper alloy, high temperature alloy, and Hastelloy as the anode and stainless steel as the cathode, immerse the treated specimen in an alkaline anodizing electrolyte, start circulating cooling, and use a DC regulated power supply in constant voltage mode. Anodize the treated specimen at a voltage of 55 V for 40 minutes. After completion, take out the specimen and rinse it with deionized water and dry it.
[0131] The surface microchannel structures of stainless steel, copper alloy, high-temperature alloy, and Hastelloy aluminum metal coating specimens prepared under this process condition are also good, and can also achieve similar improvements in boiling heat transfer efficiency.
[0132] Based on the above embodiments, it can be clearly seen that the technical solution provided by the embodiments of the present invention has the following advantages compared with the prior art:
[0133] 1. The embodiment of the present invention prepares a uniform aluminum metal coating on the surface of different base materials through magnetron sputtering technology, and addresses the technical difficulties of the prior art that it is difficult to achieve anodization reaction of the aluminum metal coating and prepare surface microchannels with uniform pore structures under alkaline conditions. A composite technology is used to realize a method for constructing a material surface microchannel structure that is not restricted by the type of base material. This method has the characteristics of high reliability and good stability.
[0134] 2. The microchannel structure prepared in the embodiment of the present invention has a higher heat transfer coefficient, and the boiling heat transfer efficiency is increased by 3 to 5 times compared with that of the base material.
[0135] 3. The method provided in the embodiment of the present invention has a wide range of applications and is applicable to the preparation of microchannels on metal surfaces of various types of stainless steel, copper alloy, high-temperature alloy, Hastelloy, etc., and is also applicable to the surfaces of structural parts with various sizes and complex shapes.
[0136] Of course, based on the spacing and bonding effect of the transition layer, even if the substrate is replaced by other substrates such as graphene, diamond, thermal conductive ceramics, etc., the aluminum surface microstructure with consistent structure and performance can also be prepared. Just pay attention to the bonding force between the film layers, which will not be elaborated here.
[0137] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. An anodic oxidation electrolyte for aluminum surface microchannel construction, characterized in that: The solute in the anodizing electrolyte includes a film-forming agent, a film-forming promoter and a film-forming auxiliary agent; The film-forming agent includes a strong base, the film-forming promoter includes an alkali metal pyrophosphate and / or an alkali metal polyphosphate, and the film-forming assistant includes an alkali metal weak acid salt.
2. The anodizing electrolyte according to claim 1, characterized in that: The film-forming agent includes any one of sodium hydroxide, potassium hydroxide, lithium hydroxide, barium hydroxide, and cesium hydroxide, or a combination of two or more thereof; And / or, the film-forming promoter includes any one of sodium pyrophosphate, potassium pyrophosphate, sodium polyphosphate, potassium polyphosphate, or a combination of two or more thereof; And / or, any one of sodium citrate, sodium acetate, sodium oxalate, potassium sodium tartrate, sodium tetraborate, or a combination of two or more thereof.
3. The anodizing electrolyte according to claim 1, characterized in that: The concentration of the film-forming agent in the anodizing electrolyte is 30 to 90 g / L; and / or, the concentration of the film-forming promoter in the anodizing electrolyte is 20 to 40 g / L; and / or, the concentration of the film-forming auxiliary agent in the anodizing electrolyte is 25 to 60 g / L; Preferably, the pH value of the anodizing electrolyte is 12-14.
4. A method for constructing aluminum surface microchannels, characterized in that: include: Contacting the surface of the substrate with the anodizing electrolyte according to any one of claims 1 to 3; The aluminum surface is used as an anode, and current is applied to the aluminum surface for anodization to form a microchannel.
5. The construction method according to claim 4, characterized in that: The aluminum surface is specifically the surface of a layer of aluminum metal coating plated on the surface of the base component.
6. The construction method according to claim 5, characterized in that: Specifically include: Providing the basic component, and coating the surface of the basic component with a transition layer; Plating the aluminum metal coating on the surface of the transition layer to form the aluminum surface; Preferably, the transition layer and the aluminum metal coating are plated by magnetron sputtering; Preferably, the material of the transition layer includes any one of titanium and chromium or a combination of two or more thereof; Preferably, the material of the basic component includes any one or a combination of two or more of metal, carbon material, ceramic and polymer material; Preferably, the thickness of the transition layer is 0.1 to 0.5 μm; And / or, the thickness of the aluminum metal coating is 5 to 20 μm.
7. The construction method according to claim 4, characterized in that: Before the anodizing, the method further comprises: The step of electrolytically polishing the aluminum surface to make the roughness Ra of the aluminum surface less than 0.3 μm.
8. The construction method according to claim 4, characterized in that: The voltage of the anodization is 10-80V; And / or, the temperature of the anodizing is 35-45°C and the time is 15-60 minutes; Preferably, the anodization is performed in a constant voltage mode.
9. The construction method according to claim 4, characterized in that: The porosity of the microchannels on the aluminum surface is between 10% and 50%.
10. The construction method according to claim 4, characterized in that: The depth of the microchannel on the aluminum surface is between 0.1 μm and 8 μm.
11. A boiling heat transfer component, characterized in that: The surface of the boiling heat transfer component has aluminum surface microchannels constructed by the construction method described in any one of claims 4 to 8.
12. Application of the boiling heat transfer component according to claim 11 in any field of electronic heat dissipation, optoelectronics, and chemical industry.
Citation Information
Patent Citations
Alkaline anodizing liquid and method for aluminum products
CN110629267A
